MEDIATING EFFECT OF POSITIVE EMOTIONS ON WORK-LIFE BALANCE AND EMPLOYEE PERFORMANCE - Yulia Novifita Sari; Shofia Amin; Dwi Kurniawan (BISMA: Jurnal Bisnis dan Manajemen, 2022)
Work-life balance is an important issue that the company must consider because it will affect productivity, satisfaction, and employee performance. This study investigates how work-life balance is related to employee performance with positive emotions as the mediation variable at PT Telkom Indonesia (Persero) Tbk-Witel Jambi. The sampling method used is probability sampling techniques with simple random sampling. The data was collected using an electronic questionnaire to 120 respondents and data analysis using smart pls 3.3.3 software. The results showed that work-life balance has a positive but insignificant relationship with performance. In contrast, the work-life balance variable has a positive and significant relationship with positive emotions, and positive emotions are positively and significantly related to employee performance. In addition, positive emotions fully mediate the relationship between work-life balance and employee performance. It implies increasing employee performance, which can be conducted through increasing positive emotions. Keywords: employee performance, positive emotions, PT. Telkom Indonesia (Persero) Tbk, work-life balance